ROLE OF WOOD WATER PROPERTIES AND LEAF DYNAMICS IN PHENOLOGY AND RESPONSE TO DROUGHT IN EVERGREEN HIMALAYAN TREE SPECIES - Poudyal, Kanta; Jha, P. K.; Zobel, D. B. (Ecoprint: An International Journal of Ecology, 2014)
Five evergreen Himalayan trees namely Castanopsis indica, Schima wallichii, Rhododendron arboreum, Quercus lanata and Q. semecarpifolia were studied for their phenological responses to drought. Wood water properties (wood moisture percentage, wood density and water in wood per volume), starch percentage content, specific leaf mass, nitrogen content in leaves and phenological processes such as leaf emergence, senescence, flowering and fruiting were measured. Measurements were taken 28 times from December 1998 to April 2001 except for the monsoon months. There was significant variation in starch percentage in zero and one year old twigs. Mean starch percentage content ranged from 23% and 17.1% (S. wallichii) to 64% and 61.7% (C. indica) in zero year and one year old twig, respectively. Wood water properties were highest in R. arboreum and lowest in C. indica. SLM showed significant variation with sampled species and mean SLM was highest in R arboreum (1.6 × 10-2 g cm-2) and lowest in S. wallichii (0.64 × 10-2 g cm-2). Mean N ranged from 1.13% (R arboreum) to 1.98% (C. indica). Reserved starch percentage and SLM had a strong effect on phenological activities. They increased during the vegetative bud break and leaf emergence and decreased during senescence. Similarly, leaf nitrogen in the studied species was at the crest of concentration during leaf initiation then declined, one in expanded leaves as the concentration became diluted by increasing cell wall material, and the other at the time of senescence by resorption. DOI: http://dx.doi.org/10.3126/eco.v19i0.9857 Ecoprint An International Journal of Ecology Vol. 19, 2012 Page: 71-84 Uploaded date: 2/14/2014